What's in and what's out in branding? A novel articulation effect for brand names - Topolinski, Sascha; Zürn, Michael; Schneider, Iris K. (Frontiers in Psychology, 2015)
The present approach exploits the biomechanical connection between articulation and ingestion-related mouth movements to introduce a novel psychological principle of brand name design. We constructed brand names for diverse products with consonantal stricture spots either from the front to the rear of the mouth, thus inwards (e.g., BODIKA), or from the rear to the front, thus outwards (e.g., KODIBA). These muscle dynamics resemble the oral kinematics during either ingestion (inwards), which feels positive, or expectoration (outwards), which feels negative. In 7 experiments (total N = 1261), participants liked products with inward names more than products with outward names (Experiment 1), reported higher purchase intentions (Experiment 2), and higher willingness-to-pay (Experiments 3a–3c, 4, 5), with the price gain amounting to 4–13% of the average estimated product value. These effects occurred across English and German language, under silent reading, for both edible and non-edible products, and even in the presence of a much stronger price determinant, namely fair-trade production (Experiment 5).